Transcriptom-based identification of a putative role for the human Acyl-CoA-Binding-Protein (ACBP) in vesicular trafficking - Vock, C.; Nitz, I.; Döring, F. (Cellular and Molecular Biology, 2010)
In the present study we performed a transcriptom-based analysis of human Acyl-CoA-Binding-Protein (ACBP) target genes. By applying Genomatix BiblioSphere expert level based co-citation filter 4 (GFG level 4) ras homolog gene family member B (RhoB) and its interacting rhophilin-2 (Rhpn2) were refined from 64 ACBP sensitive genes. TaqMan-based qRT-PCR confirmed the accuracy of the array-derived expression data. Based on Gene Ontology (GO) classification RhoB and Rhnp2 were allocated to endosomal transport and signaling processes. Thus, we suggest RhoB and Rhnp2 as ACBP target genes contributing to the proposed and evolutionary conserved function of ACBP in vesicular transport processes.